The Influence of Perceived Security and Perceived Ease of Use on Customer Satisfaction with Brand Trust as an Intervening Variable (Environmental Study of PT PLN UID Banten) - Dita Tessa Sampriani Limbong; Alimuddin Rizal Rivai (Dinasti Publisher, 2025)
The objective of this paper is to analyze the perceptions of Ease of Use and Perceived Security in relation to Customer Satisfaction, with Brand Trust positioned as a mediating variable among PLN Mobile app users. This research is motivated by the recognized significance of customer satisfaction in digital services, particularly in public service institutions such as PLN. Quantitative methods were applied, and data were collected through a survey distributed to 100 app users in UID Banten. Primary data were collected using a questionnaire. The data were then analyzed through multiple linear regression and the Sobel test to evaluate the mediating role of Brand Trust. The results of this work clearly and significantly correlated with Brand Trust, but no direct effect was detected on Customer Satisfaction. In contrast, Perceived Security was shown to significantly influence both Customer Satisfaction and Brand Trust. Furthermore, a strong direct effect of Brand Trust on Customer Satisfaction was found, and its mediating role in the relationship between Perceived Security and Customer Satisfaction was confirmed. In conclusion, it should be emphasized that enhancing Brand Trust should be prioritized to improve Customer Satisfaction, especially if supported by high levels of Security and Ease of Use. As a managerial implication, it is recommended to improve the security and user interface of the system to increase customer loyalty by strengthening brand trust.